Subtipos de receptores colinérgicos centrais envolvidos na salivação, ingestão de água e resposta pressora induzidas pela pilocarpina injetada perifericamente - Borella, Thais Leoni (2008)
The study of sialagog drugs has a relevant clinical interest for its use in patients with reduced salivatory secretion. Cholinergic agonists are a type of sialagog drug and pilocarpine is the most important cholinergic agonist drug. It is known that pilocarpine-direct action in salivatory glands muscarinic cholinergic receptors stimulate salivatory secretion. However, recent studies from our laboratory have shown that salivation induced by periferic pilocarpine seems to be dependent from central muscarinic activation. The pilocarpine-intense salivation is the well known main effect of this drug but side effects as cardiovasculars alterations and dipsogenesis are observed. Periferic injection of muscarinic agonists usually decreases periferic resistence and arterial pressure but pilocarpine-intraperitoneal (ip) injection induces an inesperate long-term pressor response associated with enhancement in mesenteric vascular resistence and salivatory glands vasodilatation, without changes in esqueletic musculature vascular resistence or heart rate. The ip pilocarpine-pressor response is atributed to an central action of this sialagog drug. The aim of the present study was to investigate central muscarinic cholinergic receptors subtype involved in salivation, water intake and pressor response induced by ip or intravenous (iv) pilocarpine injection. In addiction, the central activation induced by ip injection of pilocarpine and muscarinic receptors subtype antagonist were investigated by Fos-immunoreactivity (Fos-ir). Adult male Holtzman rats (250-300 g) with stainless steel cannulas implanted in the lateral ventricle (LV) were used. Intracerebroventricular (icv) injection of pirenzepine (M1 subtype muscarinic receptor), methoctramine (M2/M4 subtype muscarinic receptor), 4-DAMP (M1/M3 subtype muscarinic receptor) or tropicamide (M4 subtype muscarinic receptor) was performed to investigate its effect on salivation, water intake and pressor response-induced pilocarpine ip injection (4 µmol/kg of body weight (bw)). The salivation was determined in ketamine- (100 mg/kg bw) anesthetized rats using previous weighted cotton balls into oral cavity for 7 minutes. Arterial pressure and heart rate were recorded in non-anesthetized rats submitted to previous femoral artery cannulation. Fos-ir was investigated after ip injection of only pilocarpine or pilocarpine combined with pre-treatment of 4-DAMP, M1/M3 subtype muscarinic antagonist which was more efficient to block salivatory, dipsogenic and cardiovascular responses induced by ip pilocarpine. Salivatory response due to ip pilocarpine varied between 476 ± 54 to 718 ± 61 mg/7 min and was reduced by icv injection of 25, 50, 100 and 250 nmol 4-DAMP, respectively: 425.13 ± 89.73, 376.76 ± 28.01, 261.00 ± 38.28, 230.85 ± 68.61 mg/7 min. Icv injection of 0.1 and 1.0 nmol pirenzepine (0.77 ± 0.30 and 1.05 ± 0.54 ml/60 min, respectively), 50 nmol methoctramine (0.89 ± 0.30 ml/60 min) or 5 and 10 nmol 4- DAMP (1.43 ± 0.57 and 2.19 ± 0.66 ml/60 min, respectively) reduced dipsogenic effect-induced ip pilocarpine, which ranged between 3.20 ± 0.70 to 5.90 ± 1.30 ml/60 min. The pressor response-induced by ip pilocarpine varied between 40 ± 5 to 53 ± 4 mmHg and was decreased by icv injection of 100 nmol pirenzepine (9.00 ± 7.00 mmHg) or 25 and 50 nmol 4-DAMP (14.00 ± 7.00 and 3.00 ± 6.00 mmHg, respectively). Pilocarpine increased Fos-ir only in the supra-optic nuclei (SON), but not in other encephalic areas such as septal or medial lateral areas, paraventricular nuclei, subfornical nuclei, organnum vasculosum of lamina terminalis, median pre-optic nuclei had not alter its activation. The enhancement on Fos-ir in the SON induced by pilocarpine (12.8 ± 2.4 positive cell nuclei/10-2 mm2) was reduced by pre-treatment with 25 nmol 4-DAMP (3.26 ± 1.62 positive cell nuclei/10-2 mm2). Taken all together, M3 subtype central muscarinic receptor plays a role in salivation, M1 and M2 subtype central are involved in dipsogenic and M1 subtype central is involved in pressor response induced by pilocarpine. The role of central muscarinic receptor M3 subtype on dipsogenic and pressor response is not clear due to the fact 4-DAMP is not a specific antagonist, that binds M1 and M3 subtype muscarinic receptors. In addiction, these results suggest that responses evoked by periferic injection of 4 µmol/kg bw of pilocarpine could occur due to its activation through SON.